The evaluation of agreement between high-frequency ultrasonography and research diagnostic criteria for the diagnosis of temporomandibular joint internal derangements - Ravza Eraslan; Kerem Kılı; Meryem Etöz; Damla Soydan (Wolters Kluwer Medknow Publications, 2020)
Aim: The aim of this study is to compare the diagnosis of patients with temporomandibular joint (TMJ) internal derangements which had been diagnosed using Research Diagnostic Criteria/Temporomandibular Disorders (RDC/TMD) with the dynamic high resolution sonography findings. Settings and Design: Axis I section of RDC/TMD form had been applied to participants. Participants were divided into three groups as healthy TMJ, disc displacement with reduction, and disc displacement without reduction. The diagnoses had been compared with the dynamic high-resolution sonography findings. Materials and Methods: Twelve of the patients had been treated with laser therapy, whereas 13 patients were treated with stabilization splint. Seventeen patients were treated with anterior repositioning splint (n = 42). After the application of different treatment modalities, the position of the articular disc had been determined with Axis I of RDC/ TMD form and dynamic high-resolution sonography. The findings were compared and statistically analyzed. Statistical Analysis Used: Statistical analyses of data were analyzed with Turcosa Cloud (Turcosa Ltd Co, Turkey). Results: For the right TMJ, pretreatment and posttreatment ultrasonography (USG) diagnoses and RDC/ TMD clinical diagnoses were found similar (κ = 0.125-0.008). No statistically significant relationship was found (P > 0.05). For the left TMJ, pretreatment USG diagnosis and RDC/TMD clinical diagnose were found similar (κ = 0.070). No statistically significant relationship was found (P > 0.05). For the left TMJ, posttreatment USG diagnosis and RDC/TMD clinical diagnose were compared. A statistically significant difference was found (κ = 0.256). A statistically significant relationship was found (P < 0.05). Conclusions: Axis 1 of RDC/TMD form which is used for the diagnosis of internal derangements and dynamic high resolution sonography was not found in the agreement.